Persistent humoral and CD4+ TH cell immunity after mild SARS-COV-2 infection—The CoNAN long-term study - Schnizer, Clara; Andreas, Nico; Vivas, Wolfgang; Kamradt, Thomas; Baier, Michael; Kiehntopf, Michael; Glöckner, Stefan; Scherag, André; Löffler, Bettina; Kolanos, Steffi; Guerra, Joel; Pletz, Mathias W.; et al. (Frontiers in Immunology, 2023)
Understanding persistent cellular and humoral immune responses to SARS-CoV-2 will be of major importance to terminate the ongoing pandemic. Here we assessed long-term immunity in individuals with mild COVID-19 up to one year after a localized SARS-CoV-2 outbreak. CoNAN was a longitudinal population-based cohort study performed 1.5 months, 6 months and 12 months after a SARS-CoV-2 outbreak in a rural German community. We performed a time series of five different IgG immunoassays assessing SARS-CoV-2 antibody responses on serum samples from individuals that had been tested positive after a SARS-CoV-2 outbreak as well as in control individuals who had a negative PCR result. These analyses were complemented with the determination of spike-antigen specific TH cell responses in the same individuals. All infected participants presented as asymptomatic or mild cases. Participants initially tested positive for SARS-CoV-2 infection either with PCR, antibody testing, or both had a rapid initial decline in the serum antibody levels in all serological tests but showed a persisting TH cell immunity as assessed by the detection of SARS-CoV-2 specificity of TH cells for up to one year after infection. Our data support the notion of a persistent T cell immunity in mild and asymptomatic cases of SARS-CoV-2 up to one year after infection. We show that antibody titers decline over one year, but considering several test results, complete seroreversion is rare.